2009
DOI: 10.1063/1.3261752
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the resonant growth of harmonics on the electron density in capacitively coupled plasma

Abstract: The growth of harmonics is known to occur under the condition of plasma series resonance (PSR). In an actual plasma process chamber, the external circuit also affects the PSR. We experimentally demonstrated the resonant growth of the third and fourth harmonics by tuning a variable capacitor attached to the electrode, and investigated the influence of the growth on the electron density. We observed significant increases in electron density as the amplitude of harmonics grows. The result clearly shows that nonli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Of course, the amplitude of these PSR oscillations is very small compared to the total current amplitude due to the relatively small asymmetry. This is different from the "classical" scenario of the PSR self-excited in geometrically asymmetric discharges [65,[86][87][88][89][90][91], where usually ε 1 and NERH (Nonlinear Electron Resonance Heating) gives a large contribution in the electron heating [65,87,92]. Due to the symmetry parameter ε shown in Fig.…”
Section: Control Of the Self-excitation Of Psr Oscillationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of course, the amplitude of these PSR oscillations is very small compared to the total current amplitude due to the relatively small asymmetry. This is different from the "classical" scenario of the PSR self-excited in geometrically asymmetric discharges [65,[86][87][88][89][90][91], where usually ε 1 and NERH (Nonlinear Electron Resonance Heating) gives a large contribution in the electron heating [65,87,92]. Due to the symmetry parameter ε shown in Fig.…”
Section: Control Of the Self-excitation Of Psr Oscillationsmentioning
confidence: 98%
“…The self-excitation of the plasma series resonance (PSR) is an important issue in asymmetric capacitive discharges operated at low pressures, because it enhances the electron heating [65,67,[73][74][75][76][86][87][88][89][90][91][92]. Due to Eq.…”
Section: Control Of the Self-excitation Of Psr Oscillationsmentioning
confidence: 99%
“…1(a) and 1(b)]. Discrepancies in the absolute magnitude of B φ;n , shown in Table I, could be due to neglect of external circuit in the model [32] and/or a small difference between the measured voltage and the actual voltage applied on the electrode edge. Figures 1(c) and 1(d) and Figs.…”
mentioning
confidence: 99%
“…1;2 It has been shown by means of careful measurements that the resonant increase of harmonics in the plasma current (even in the case of strongly sinusoidal driving voltage) leads to an increase of the electron density. 3 It has been also shown that the external circuit of the system, i.e., the matching unit, stray capacitance, and cable inductance, significantly influence the resonant behavior of the system. Therefore, it is possible to increase the electron density by detuning the resonances using an additional external circuit (under constant conditions).…”
mentioning
confidence: 99%